Optimization of flat solar collectors area for hot water systems - Кравченко, Владимир Петрович; Кравченко, Егор Владимирович (Technology audit and production reserves, 2015)
In materials for planning of solar hot water heating systems (SHWHS) at determination of solar collector’s area the mode of operations and losses of warmth at transmission to coolant are not taken into account. Optimization of solar collector’s area on the criterion of a minimum of the annual resulted expenses in the divalent setting for a hot water-supply taking into account these factors is taking place. The annual expenses were determined taking into account an ecological constituent that included the payment for harmful extras according to the Tax code of Ukraine and Kyoto protocol. It is got as a result of researches, that area of collectors for SHWHS working during the warm half of year, it is necessary to determine on specific insolation in June. The angle of collectors tilt must be equal to 25°. For SHWHS working the whole year round, the angle of collectors tilt is equal to 40°, and the area of collectors must be determined on specific insolation in May. The got results promote efficiency of the SHWHS use for a hot water-supply in the south of Ukraine conditions.